99 - ENTRAINMENT BRAIN WAVES (BWE): A LITERATURE REVIEW ON THE EFFECTS OF SYNTHESIZING PHOTIC AND HEARING IN VARIANTS OF MOTOR AND COGNITIVE BEHAVIOR HUMAN (Fiep Bulletin - online, 2011)
Evidence in the literature show positive results regarding the use of brain stimulation, the effect of synthesis photic / auditory dysfunction in motor, cognitive and behavioral in various everyday situations common to several particular sample groups. The rationale for the application is established on the theoretical assumption oriented principle by Siever (1999), whose reference point is that this stimulation is projected via neurons of the reticular formation, joining the groups own neurochemicals in the brain stem and hence modulating neurons sub cortical and articulation appropriate to the integrative process of learning, memory and attention. The reference to the relationship that is the balance between the hemispheres, a substrate for an optimized disposition of the brain to integrate and enhance stimulus appropriate responses. These precepts have guided the structure of the present study, which reviewed a series of studies in line with the objective of adding bases of theoretical and practical guidance for future research.
Keywords: Brain waves; photic and auditory stimulation; behavior